Microstructural properties of M7C3 eutectic carbides in a Fe-Cr-C alloy - Buytoz, S (Elsevier Science Bv, 2006)
The rnicrostructure of Fe-Cr-C coatings was investigated with optical microscope (OP), scanning electron microscope (SEM), electron dispersive spectrograph (EDS), respectively. The coatings were formed by means of gas tungsten arc welding method on the AISI 4340 steel. The microstructures of the coatings are found to compose of primary M7C3 carbides in eutectic of austenite matrix. The hypereutectic microstructure consisted Of M7C3 and M7C3 + austenite (gamma). The hardness values Of M7C3 carbides varied between 1050 and 1500 HV, while the hardness of M7C3+austenite (gamma) matrix measured between 500 and 750 HV. The lower hardness of matrix of the coating microstructure was related to the relatively low concentrations of Cr and C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: M7C3 carbides; retained austenite; coating